Is Regional Mobility Control Effective in Minimising COVID-19 Spread? Lessons Learned From Jakarta’s Large-Scale Social Restriction - Azmi, Fisca Rizkiani; Kusumasari, Bevaola (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2021)
In times of crisis such as a pandemic, local governments serve a pivotal role as first-hand responders in managing emergencies in local areas, with the expectation of an effective policy to implement. Notwithstanding, there are limited literature studies of emergency management on local governments, concentrating on identifying policy effectiveness by the implementation in the field. This article emphasizes the effectiveness of local policy implementation in managing the emergency of the COVID-19 pandemic in the Jakarta area, with the centralization on Large-Scale Social Restriction as the case study. The objective is to provide lessons related to coronavirus for the government to evaluate future policies. Using secondary data analysis as a method, the findings would diagnose the empirical stratum of the local government's implementation in handling COVID-19, which defines the policy's effectiveness. The result of this analysis is intended to propound insights to public managers in the hope of receiving a more profound comprehension of their possibility and improving their enactment in handling a crisis.